Facilitating Faculty Mentoring within a Community of Practice Model - Emily R. Smith; Patricia E. Calderwood; Paula Gill Lopez (Academic Chairpersons Conference Proceedings, 2015)
This roundtable explores ways in which department chairs might effectively facilitate faculty mentoring through a community of practice model. We explicate the central components of a community of practice model for mentoring and illustrate how this model serves to build trust and break down traditional expert-novice boundaries.
Keywords: mentoring; community of practice; higher education; identity; departments